Hepatic and portal vein transection by vascular stapler in open living donor hepatectomy – A retrospective cohort study. (June 2022) - Obed, Doha; Jarrad, Anwar; Othman, Mohammad Ibrahim; Siyam, Mahmoud; Bashir, Abdalla; Obed, Aiman
Abstract: Background: In an effort to increase donor safety in living donor liver transplantation, the utilization of vascular staplers for the division of the right portal and hepatic veins in patients undergoing right lobe liver donation for living donor liver transplantation (LDLT) was implemented. In here we report our experience with vascular staplers in patients undergoing LDLT and evaluate the subsequent feasibility and safety for donors. Material and methods: 17 cases of living donor liver transplant were retrospectively analyzed. The right portal vein was transected directly at the bifurcation of the main portal vein, the right hepatic vein was resected directly at the wall of the inferior vena cava using a vascular stapler device. Results: We registered a complication rate of 41.2% (7 donors). According to the Clavien-Dindo classification, grade II and grade III complications were each observed in 5.9% and grade IIIb complications in 29.4%, whereas catastrophic bleeding, complications with residual disability or the necessity of re-laparatomy did not occur. Upon 6 weeks, all donors were able to return to their previous occupation in fully recovered condition. Conclusions: The utilization of vascular staplers in donors during open LDLT presents an encouraging alternative to manual over-sewing of vascular stumps. Apart from its timesaving aspect, the technique reduces the potential risk of life-threatening clamp slippage with subsequent uncontrolled blood loss. Highlights: Portal or hepatic vein injuries are severe complications in liver transplant. Vascular staplers were used in an effort to increase donor safety. Hepatic or portal vein injuries or bleeding did not occur when using staplers. Vascular staplers may be a safe alternative to manual vascular sewing. Their use may be timesaving and reduce the risk of clamp slippage.